2019
DOI: 10.1016/j.immuni.2019.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident Group 2 Innate Lymphoid Cells Differentiate by Layered Ontogeny and In Situ Perinatal Priming

Abstract: The perinatal period is a critical window for distribution of innate tissue-resident immune cells within developing organs. Despite epidemiologic evidence implicating the early-life environment in the risk for allergy, temporally controlled lineage tracing of group 2 innate lymphoid cells (ILC2s) during this period remains unstudied. Using complementary fate-mapping approaches and reporters for ILC2 activation, we show that ILC2s appeared in multiple organs during late gestation like tissue macrophages, but, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
269
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(295 citation statements)
references
References 61 publications
25
269
0
1
Order By: Relevance
“…33 A recent publication showed that perinatal signals leading to expansion of neonatal ILC2s are important to maintain even the adult pool of ILC2s. 38 This perinatal expansion of ILC2s was independent of commensal microbiota as it occurred also in GF mice. As interactions between an individual SPF consortium and a defined diet are very complex, it is not unlikely that a combination of dietary and microbial signals contributes to this event.…”
Section: Ilc Development and Microbiota In Prenatal And Early Lifementioning
confidence: 84%
See 1 more Smart Citation
“…33 A recent publication showed that perinatal signals leading to expansion of neonatal ILC2s are important to maintain even the adult pool of ILC2s. 38 This perinatal expansion of ILC2s was independent of commensal microbiota as it occurred also in GF mice. As interactions between an individual SPF consortium and a defined diet are very complex, it is not unlikely that a combination of dietary and microbial signals contributes to this event.…”
Section: Ilc Development and Microbiota In Prenatal And Early Lifementioning
confidence: 84%
“…A recent publication showed that perinatal signals leading to expansion of neonatal ILC2s are important to maintain even the adult pool of ILC2s . This perinatal expansion of ILC2s was independent of commensal microbiota as it occurred also in GF mice.…”
Section: Ilc Development and Microbiota In Prenatal And Early Lifementioning
confidence: 96%
“…Consistent with a more innate immune function, neonatal T cells were shown to produce tumor necrosis factor (TNF) and CXCL8 . Age‐dependent qualitative differences have also been identified within the ILC compartment . EOMES + natural killer cells with a robust effector phenotype populate the human neonatal intestine and might provide protection until T‐cell effector cells have matured …”
Section: Towards the Concept Of A Temporally Layered Postnatal Establmentioning
confidence: 99%
“…91,97 Age-dependent qualitative differences have also been identified within the ILC compartment. 98 EOMES + natural killer cells with a robust effector phenotype populate the human neonatal intestine and might provide protection until T-cell effector cells have matured. 99 Clearly, developmental mechanisms contribute significantly to the initial adaptation to microbial exposure.…”
Section: Postnatal Maturation Of the Neonatal Innate Immune Systemmentioning
confidence: 99%
“…which play important roles in initiating type 2 immunity (1). They are enriched in barrier locations such as the lung, intestine and skin (2). They respond to signals released by tissue damages, namely IL-25, IL-33 and TSLP, and produce type 2 cytokines primarily consisting of IL-5, IL-9 and IL-13 (3).…”
Section: Group 2 Innate Lymphoid Cells (Ilc2s) Are a Subset Of Innatementioning
confidence: 99%